FAMILY REHARMONIZATION AFTER THE COVID-19 PANDEMIC FROM THE PERSPECTIVE OF MUBȂDALAH - Zezen Zainul Ali; Annisa Wulandari (Marwah: Jurnal Perempuan, Agama dan Jender, 2023)
This research will discuss efforts to reharmonize families after being affected by the COVID-19 pandemic in the physical, social, and economic aspects of the family. The pandemic has an impact on household harmony and can even lead to divorce. So, it is necessary to make efforts to reharmonize the family by using the mubȃdalah approach. This research is field research, with a descriptive-qualitative research method using the mubȃdalah approach. So that the research results found that the co-19 pandemic had an impact on family harmony which was influenced by aspects namely spirituality, communication, psychology, and economics. Rebuild harmony (reharmonization) can be done by increasing faith in Allah SWT, building patience and comfort, prejudging, and treating well towards partners, building harmony, and building good communication and deliberation. If this is done, it will have implications for household harmonization which is getting better after being affected by the Covid-19 pandemic.